Perceptions of the Accessibility of the Universitas Negeri Padang Library and Publishing Repository among Library and Information Science Students of the 2022 Cohort Using the UTAUT Model - Fini Alya Putri; Marlini Marlini (Darul Yasin Al Sys, 2026)
Research on technology acceptance in higher education repository services has continued to expand; however, studies specifically examining repository accessibility through the Unified Theory of Acceptance and Use of Technology (UTAUT) remain limited, particularly among Library and Information Science students. This study aimed to describe students’ perceptions of the accessibility of the Repository of the Library and Publishing Center of Universitas Negeri Padang (UNP) using the UTAUT framework. A quantitative descriptive approach was employed, involving 48 active students from the 2022 cohort of the Library and Information Science Study Program selected through simple random sampling. Data were collected using a Likert-scale questionnaire developed based on four primary UTAUT indicators: performance expectancy, effort expectancy, social influence, and facilitating conditions. The data were analyzed using descriptive quantitative techniques, including frequency distribution, percentage analysis, and mean score calculation. The findings showed that all indicators were categorized as good, with mean scores of 2.97 for performance expectancy, 3.02 for effort expectancy, 3.01 for social influence, and 3.01 for facilitating conditions. These results indicate that the UNP repository is perceived as beneficial for supporting academic activities, relatively easy to use, supported by the academic environment, and facilitated by adequate infrastructure and services. The study concludes that the Repository of the Library and Publishing Center of Universitas Negeri Padang provides accessible academic information services for students. These findings contribute to the literature on technology acceptance in higher education repository services and imply the need to improve search features, enhance technical support, and strengthen repository socialization programs to optimize digital information services in higher education institutions.